A 2q24.2 microdeletion containing TANK as novel candidate gene for intellectual disability. Issue 5 (25th February 2019) - Karoglan, Ante; Schanze, Denny; Bär, Claudia; Muschke, Petra; Zenker, Martin; Schanze, Ina
Abstract : Interstitial deletions within the chromosomal region 2q24.2 have already been linked to intellectual disability (ID) in the past. In most cases the described patients showed a syndromic form of ID associated with large deletions containing multiple genes. Here we describe a family with two siblings with mild non‐syndromic ID. They shared the same 564 kb deletion in the chromosomal region 2q24.2 containing only the TANK gene, which was inherited from the similarly affected father, thus suggesting haploinsufficiency of TANK as a novel cause of non‐syndromic ID. TANK encodes the TRAF family member‐associated NF‐kappa‐B activator (OMIM #603893), which is expressed in many tissues. It functions as an adapter protein that interacts with the NF‐kappa‐B pathway and SOX11, an essential transcription factor in regeneration, survival and differentiation of the neuronal system. TANK has not been linked to ID or other human diseases before. To further elucidate the role of TANK in non‐syndromic ID, we screened a cohort of 288 TANK deletion negative non‐syndromic mental retardation patients for TANK mutations without identifying any pathogenic variant.